1,2,3 - Yoshi (Saxonville, MA : Picture Book Studio, 1991)
A cumulative counting tale in which one inchworm precipitates busy activity among an increasing number of animals. Hidden in each picture is a numeral, diguised among the shapes of the natural world.
Keywords: Animals -- Fiction; Counting; Picture puzzles